KUALITAS PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Febri Yuliani, R. Vivi Olivia Reindra Lestari, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2020)
Policy Quality Of Public Services In Dinas Kependudukan Dan Pencatatan Sipil Of Pekanbaru City. This study departs from the problem of the poor quality of public service at the Disdukcapil in Pekanbaru, starting from the non-responsiveness of public complaint services, the condition of narrow spaces, non-functioning waiting room facilities and infrastructure, as well as the lack of certainty over the completion of administrative services. This research is intended to analyze the quality of public services in Pekanbaru City Disdukcapil service and find out what factors are hampering the improvement of the quality of public services. This study uses a descriptive qualitative research method approach. Primary data obtained directly through interviews from informants, namely the Staff, the Heads of Divisions and the Heads of Sub Divisions in the Disdukcapil Pekanbaru City as the implementor. From the results of this study it can be seen that the quality of public services in Pekanbaru City Disdukcapil service has not, this condition is known from the inadequate physical condition of the building, there are still weak employees at work and there is no certainty of time given to the community when their affairs are finished.